Endovascular thrombectomy for basilar artery occlusion stroke: Analysis of the German Stroke Registry‐Endovascular Treatment. (22nd February 2023) - Feil, Katharina; Berndt, Maria Teresa; Wunderlich, Silke; Maegerlein, Christian; Bernkopf, Kathleen; Zimmermann, Hanna; Herzberg, Moriz; Tiedt, Steffen; Küpper, Clemens; Wischmann, Johannes; Schönecker, Sonja; Dimitriadis, Konstantin; et al.
Abstract: Background and purpose: Acute ischemic stroke due to basilar artery occlusion (BAO) causes the most severe strokes and has a poor prognosis. Data regarding efficacy of endovascular thrombectomy in BAO are sparse. Therefore, in this study, we performed an analysis of the therapy of patients with BAO in routine clinical practice. Methods: Patients enrolled between June 2015 and December 2019 in the German Stroke Registry‐Endovascular Treatment (GSR‐ET) were analyzed. Primary outcomes were successful reperfusion (modified Thrombolysis in Cerebral Infarction [mTICI] score of 2b‐3), substantial neurological improvement (≥8‐point National Institute of Health Stroke Scale [NIHSS] score reduction from admission to discharge or NIHSS score at discharge ≤1), and good functional outcome at 3 months (modified Rankin Scale [mRS] score of 0–2). Results: Out of 6635 GSR‐ET patients, 640 (9.6%) patients (age 72.2 ± 13.3, 43.3% female) experienced BAO (median [interquartile range] NIHSS score 17 [8, 27]). Successful reperfusion was achieved in 88.4%. Substantial neurological improvement at discharge was reached by 45.5%. At 3‐month follow‐up, good clinical outcome was observed in 31.1% of patients and the mortality rate was 39.2%. Analysis of mTICI3 versus mTICI2b groups showed considerable better outcome in those with mTICI3 (38.9% vs. 24.4%; p  = 0.005). The strongest predictors of good functional outcome were intravenous thrombolysis (IVT) treatment (odds ratio [OR] 3.04, 95% confidence interval [CI] 1.76–5.23) and successful reperfusion (OR 4.92, 95% CI 1.15–21.11), while the effect of time between symptom onset and reperfusion seemed to be small. Conclusions: Acute reperfusion strategies in BAO are common in daily practice and can achieve good rates of successful reperfusion, neurological improvement and good functional outcome. Our data suggest that, in addition to IVT treatment, successful and, in particular, complete reperfusion (mTICI3) strongly predicts good outcome, while time from symptom onset seemed to have a lower impact.